Asymmetric Causal Linkages Between Financial Development and Ecological Footprint: Evidence From G7 and E7 Economies - Tuncel, Mert Baran; Yaman, Serdar (Wiley, 2025)
This study investigated the asymmetric causal relationship between financial development and the ecological footprint in G7 and E7 countries from 1992 to 2019 using the Hatemi-J panel asymmetric causality test. Motivated by the increasing global concern about how financial systems interact with environmental sustainability, the study aimed to provide a comparative understanding between advanced and emerging economies. Another objective of the study is to test the validity of the Environmental Kuznets Curve (EKC) hypothesis across different development levels. The results show that financial development and the ecological footprint are asymmetrically linked in G7 economies but symmetrically linked in E7 economies. The EKC is valid for E7 countries, while the Pollution Halo and Pollution Haven hypotheses hold for G7 and E7, respectively. By integrating financial asymmetry into environmental causality analysis, this study contributed to the literature with a novel empirical approach. Empirical evidence suggested that promoting green finance, renewable energy, and energy efficiency can align financial growth with sustainability, while emerging economies should prioritize institution-building to align financial expansion with environmental objectives, and developing green bond markets, carbon trading systems, and transparent environmental disclosure frameworks.
Keywords: ecological footprint; environmental technologies; financial development; foreign direct investment; renewable energy consumption; sustainable development